Thermo-economic performance analysis of a gas turbine generator equipped with a pressurized and an atmospheric solid oxide fuel cell. (15th March 2017) - Pirkandi, Jamasb; Mahmoodi, Mostafa; Ommian, Mohammad
Highlights: Two different configurations for SOFC&GT hybrid system were presented. Hybrid system with two series pressurized fuel cell was evaluated. Hybrid system with one pressurized and one atmospheric fuel cell was investigated. These systems compared and analyzed based on the thermodynamic and thermo-economic models. Abstract: The main objective of this research is to introduce and present two different configurations for hybrid gas turbine-fuel cell systems of direct type and to analyze these systems based on the thermodynamic and thermo-economic models. In the first proposed design, two fuel cells are situated at the upstream of turbine and operate at a specific pressure; while in the second design, one of the cells is transferred to the downstream of turbine, and it works under atmospheric pressure. Also, in the economic analyses performed in this research, a simple economic model and the Total Revenue Requirement model are employed to compute the electricity generation price and the other relevant expenses. The examination of the two proposed systems shows that the hybrid system with one pressurized and one atmospheric fuel cell (the second design) enjoys a higher efficiency and power generation capacity, but at the same time, it has greater exergy destruction and irreversibility rates. The results also indicate that this design generates more pollution compared to the first design. From an economical point of view, the generated electricity price and the purchase, installation and startup costs of both systems are almost the same, and have no significant difference.